(untitled) (The Strategic Review for Southern Africa, 2020)
Debates on whether reconciliation is taking place and particularly the issue of inclusive development continue in South Africa. Reconciliation is understood as a process whereby different population groups in South Africa peacefully coexist and restore amicable relations which were fractured by colonialism and apartheid. Inclusive development has to do with the socio-economic transformation that involves, or rather benefits all the peoples of a country. Socio-economic transformation is considered slow since the dawn of democracy, with nation-building, development, freedom, and related objectives having suffered in post-apartheid South Africa. The notions of justice and inclusivity require comprehensive analysis, especially many years after the formal end of apartheid in 1994. The paper examines development and reconciliation, in seeking an explanation for what appears to be a changing political landscape in South Africa, epitomised by the decline in the number of votes that the governing party, the African National Congress (ANC), is receiving since 2009 while the Economic Freedom Fighters, a relatively new party, is gaining traction. It is argued that the slow pace of inclusive development and weak reconciliation are compromising the ANC, resulting in the evolution of the political landscape in South Africa. Essentially, the inability to improve reconciliation has resulted in weak inclusive development and makes it difficult for South Africa to become a nation.